An Evaluation of the Output of Rubber Forest Plantation - Liew, Siong Ching (2001)
The wood based industry is important to Malaysia The timber sector continues to be major contributor to the economic sector, generating about 4.5% of the country's GDP and has a workforce of 240 000 people. Export of timber products amounted to about US$4.5 billion in 1999 or 5.4% of the country's foreign receipts. Downstream manufacturing especially furniture fabrication saw the shift from over-dependence on solid wood from the natural forest species to Rubberwood and panel products such as MDF and particleboard. Presently, about 85% of all wooden furniture exported is made of Rubberwood Rubberwood is the main raw material used for the booming wood-based industry in Malaysia. However, the supply issue of the Rubberwood resource is intensely debated in Malaysia. Wood-based industry claim that there is a shortage of supply, but the related government agencies argue that the short supply is simply due to logistic problem. The implications of Rubberwood sawntimber shortage are far reaching because it affects higher production costs low productivity and inconsistency quality in furniture production. The objective of this study is to evaluate availability of Rubberwood supply for the wood-based industry next few year and also viability of rubber forest plantation. This study found that, the amount of Rubberwood is not enough to support the Furniture Industry in Malaysia. Beside that, from the study examine the viability of investment in establishing short-cycle (15 years) rubber forest plantations fro extraction of both latex and wood as well as that of plantations established solely for extraction of timber, both IIR and NPV value for rubber forest plantations with wood and latex extraction are higher than the plantations with wood extraction. However, Ble Ration for forest plantations with wood extraction is higher than the forest plantations with wood and latex extraction. This means that, we can get more revenue from the plantations with wood and latex extraction. Therefore, the return from the wood only option is poorer than the latex and wood option.